2023
DOI: 10.1172/jci.insight.163403
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar type II epithelial cell FASN maintains lipid homeostasis in experimental COPD

Li-Chao Fan,
Keith McConn,
Maria Plataki
et al.

Abstract: Alveolar epithelial type II (AEC2) cells strictly regulate lipid metabolism to maintain surfactant synthesis. Loss of AEC2 cell function and surfactant production are implicated in the pathogenesis of the smoking-related lung disease chronic obstructive pulmonary disease (COPD). Whether smoking alters lipid synthesis in AEC2 cells and whether altering lipid metabolism in AEC2 cells contributes to COPD development are unclear. In this study, high-throughput lipidomic analysis revealed increased lipid biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Signaling pathways include immune system [109], signal transduction [110], extracellular matrix organization [111], adaptive immune system [112], neutrophil degranulation [113], innate immune system [114], metabolism [115], diseases of metabolism [116] and Hemostasis [117] were responsible for advancement of COPD. PTGS2 [118], IL6 [119], CSF3 [120], CXCL8 [121], CXCL1 [122], SOCS3 [123], CCL3 [124], CCL5 [125], VCAM1 [126], CXCL13 [127], CXCL5 [128], CXCL12 [129], FGG (fibrinogen gamma chain) [130], IL1B [131], AREG (amphiregulin) [132], SERPINE1 [133], OSM (oncostatin M) [134], CCL11 [135], MFAP4 [136], APLN (apelin) [137], IL1RN [138], IFNG (interferon gamma) [139], CX3CL1 [140], CDKN1A [141], ICAM1 [142], SNAI1 [143], CD34 [144], IL33 [145], FASLG (Fas ligand) [146], FGF7 [147], TNF (tumor necrosis factor) [148], GDF15 [149], CCL22 [150], IL2 [151], CXCR6 [152], KLF5 [153], MCL1 [154], SRF (serum response factor) [155], FABP4 [156], CYP2C19 [157], CXCR4 [158], FOXC1 [159], EPHX1 [160], ANXA1 [161], DUSP6 [162], CPA3 [163], MYH10 [164], ICOS (inducible T cell costimulator) [165], CD1C [166], CD96 [167], S100A9 [168], FKBP5 [169], HMOX1 [170], PRTN3 [171], MARCO (macrophage receptor with collagenous structure) [172], STAB1 [173], SIGLEC9 [174], SLC11A1 [175], BPI (bactericidal permeability increasing protein) [176], PGF (placental growth factor) [177], FASN (fatty acid synthase) [178], S100A4 […”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include immune system [109], signal transduction [110], extracellular matrix organization [111], adaptive immune system [112], neutrophil degranulation [113], innate immune system [114], metabolism [115], diseases of metabolism [116] and Hemostasis [117] were responsible for advancement of COPD. PTGS2 [118], IL6 [119], CSF3 [120], CXCL8 [121], CXCL1 [122], SOCS3 [123], CCL3 [124], CCL5 [125], VCAM1 [126], CXCL13 [127], CXCL5 [128], CXCL12 [129], FGG (fibrinogen gamma chain) [130], IL1B [131], AREG (amphiregulin) [132], SERPINE1 [133], OSM (oncostatin M) [134], CCL11 [135], MFAP4 [136], APLN (apelin) [137], IL1RN [138], IFNG (interferon gamma) [139], CX3CL1 [140], CDKN1A [141], ICAM1 [142], SNAI1 [143], CD34 [144], IL33 [145], FASLG (Fas ligand) [146], FGF7 [147], TNF (tumor necrosis factor) [148], GDF15 [149], CCL22 [150], IL2 [151], CXCR6 [152], KLF5 [153], MCL1 [154], SRF (serum response factor) [155], FABP4 [156], CYP2C19 [157], CXCR4 [158], FOXC1 [159], EPHX1 [160], ANXA1 [161], DUSP6 [162], CPA3 [163], MYH10 [164], ICOS (inducible T cell costimulator) [165], CD1C [166], CD96 [167], S100A9 [168], FKBP5 [169], HMOX1 [170], PRTN3 [171], MARCO (macrophage receptor with collagenous structure) [172], STAB1 [173], SIGLEC9 [174], SLC11A1 [175], BPI (bactericidal permeability increasing protein) [176], PGF (placental growth factor) [177], FASN (fatty acid synthase) [178], S100A4 […”
Section: Discussionmentioning
confidence: 99%
“…4 5 20 The major site of fat metabolism is in alveolar epithelial cells in lung, ATII cells strictly regulate lipid metabolism to maintain surfactant synthesis. 21 Fatty acids are a key component of surfactant, and their metabolism in alveolar epithelial cells is essential to produce this substance. We showed that FABP1 colocalised with the marker of type II alveolar epithelial cells SPC, and the expression of SPC increased while the restoration of FABP1 (figure 5), hinting it can increase the production of surfactant, up-regulate the expression of SPC and promote the regeneration of alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipids are an important component of PSs, which reduce alveolar surface tension and prevent alveolar atrophy during exhalation. PSs are mainly synthesized by Alveolar type II epithelial (AT2) cells, but the number of proliferating AT2 cells in the lung tissue of premature infants with BPD is reduced ( 5 , 6 ). Therefore, the synthesis of PS in premature infants with BPD may be hindered.…”
Section: Introductionmentioning
confidence: 99%